Effect of the dispersibility of BaTiO3 nanoparticles in BaTiO3/polyimide composites on the dielectric properties - Choi, Seung-Hoon; Kim, Il-Doo; Hong, Jae-Min; Park, Ki-Hong; Oh, Seong-Geun (ELSEVIER, 2007)
We have investigated the effect of coupling agents with different organic moiety on the dielectric properties of polyimide/BaTiO3 (70 nm) composite films. INAAT (isopropyl tris(N-amino-ethyl aminoethyl)titanate, KR 44) and APTS (3-amino-propyl-triethoxysilane) were used as coupling agents, respectively, for homogeneous dispersion of BaTiO3 particles into a polyimide matrix. The composite films were prepared by pyromellitic dianhydride (PMDA) and 4,4'-oxydianiline (ODA)-based polyimide. Enhanced dispersion of BaTiO3 particles was obtained by the use of INAAT with more organic moiety compared to that afforded by APTS. The polyimide composite with BaTiO3 particles (BaTiO3 content at 50 vol.%) treated by INAAT showed an increased dielectric constant of 19.03 while retaining an appropriate dielectric loss of 0.0109, as compared to the dielectric constant (14.64) of polyimide/APTS-treated BaTiO3 composite. The results of this work demonstrate the potential use of an INAAT coupling agent with more organo functional groups for obtaining enhanced dielectric properties in a polyimide/BaTiO3 composite for application in an embedded capacitor. (c) 2006 Elsevier B. V. All rights reserved.
Keywords: FILMS